Art beyond representation: The performative power of the image - Bolt, Barbara (London I.B.Tauris, 2004)
Refuting the assumption that art is a representational practice, Bolt's striking argument engages with the work of Heidegger, Deleuze and Guattari, C.S.Peirce and Judith Butler to argue for a performative relationship between art and artist. Drawing on themes as diverse as the work of Cézanne and of Francis Bacon, the transubstantiation of the Catholic sacrament and Wilde's novel The Picture of Dorian Gray, she challenges the metaphor of light as enlightenment, reconceiving this revealing light as the blinding glare of the Australian sun, and suggests that too much light may in fact reveal nothing. Finally she asks: how does an embodied practice fare within the culture of conceptual art?